2007
DOI: 10.1002/pssb.200675104
|View full text |Cite
|
Sign up to set email alerts
|

Cathodoluminescence of single ZnO nanorod heterostructures

Abstract: Optical properties of ZnO-based single nanorods are probed by cathodoluminescence (CL) measurements at T = 5 K. We observe a variation of the ZnO near band edge CL by three orders of magnitude along the nanorod axis, accompanied by a spectral blueshift of 10 -30 meV. This indicates a rather poor structural quality of the nanorod bottom part, close to the substrate. ZnO/ZnMgO quantum wells grown on top of ZnO nanorods are found to exhibit much stronger confinement effects as compared to their twodimensional cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 5 publications
1
15
0
Order By: Relevance
“…These defects largely suppress UV emission. Similarly, Piechal et al 28 found that a large amount of lattice defects at the bottom of ZnO nanorods grown on a substrate led to observable variations in CL transitions. In Figure 3c,d, it can be seen that the luminescence from sidewalls (between the rods, Figure 3d) was stronger than that from the top of the rod.…”
Section: Resultsmentioning
confidence: 96%
“…These defects largely suppress UV emission. Similarly, Piechal et al 28 found that a large amount of lattice defects at the bottom of ZnO nanorods grown on a substrate led to observable variations in CL transitions. In Figure 3c,d, it can be seen that the luminescence from sidewalls (between the rods, Figure 3d) was stronger than that from the top of the rod.…”
Section: Resultsmentioning
confidence: 96%
“…Before CL measurements the nanorod SQWs were detached from the Si substrate and dispersed on a Si substrate. Measurements were performed at 5 K with a CL spectroscopy attached to an electron microscopy chamber, as described elsewhere 27. The electron beam acceleration voltage and current were 30 kV and 100 pA, respectively, when the electron beam diameter was estimated to be 50 nm.…”
Section: Methodsmentioning
confidence: 99%
“…[23][24][25][26][27][28] The UV peak observed in this study can be ascribed to the near band edge emission (NBE: 385 nm), and the visible peak is ascribed to the deep level emissions (DE: 550 nm). Chang et al found that stoichiometry is the key to strong CL emission near the band edge (382 nm), while a high oxygen-vacancy concentration leads to strong green emission around 550 nm.…”
Section: Spatially Resolved Cathodoluminescence From Individual Nanobmentioning
confidence: 99%
“…[27a] Another study by Dang and co-workers indicated that large lattice defects at the bottom of nanowires, grown on a substrate, leads to variation in CL transitions. [28] Thus, the UV peak in the present sample is the NBE peak whereas the visible emission may be caused by oxygen vacancies.…”
Section: Spatially Resolved Cathodoluminescence From Individual Nanobmentioning
confidence: 99%